2014
DOI: 10.1021/nn501962y
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Biosensor Based on Localized Surface Plasmon Resonance for Monitoring Small Molecule–Protein Interaction

Abstract: We report an optical sensor based on localized surface plasmon resonance (LSPR) to study small-molecule protein interaction combining high sensitivity refractive index sensing for quantitative binding information and subsequent conformation-sensitive plasmonactivated circular dichroism spectroscopy. The interaction of R-amylase and a small-size molecule (PGG, pentagalloyl glucose) was log concentration-dependent from 0.5 to 154 μM. In situ tests were additionally successfully applied to the analysis of real wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 67 publications
3
49
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] These nanoparticles display unique localized surface plasmon resonance (LSPR) properties 1,4,6,13 originating from the coherent oscillation of conduction electrons on their surface when excited by incident photons. In addition to size and shape of a nanoparticle, the local dielectric environment modulates its LSPR frequency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] These nanoparticles display unique localized surface plasmon resonance (LSPR) properties 1,4,6,13 originating from the coherent oscillation of conduction electrons on their surface when excited by incident photons. In addition to size and shape of a nanoparticle, the local dielectric environment modulates its LSPR frequency.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 It is well established that the refractive index of the surrounding environment affects the wavelength of the LSPR. 37 To ascertain the optimal conditions for the aptamer-based assays, the sensitives of LSPR measurements in liquid (buffer) and air were compared by measuring the LSPR wavelength shift (Δ λ ) at several points in the assembly and capture process in both PBS and air.…”
Section: Resultsmentioning
confidence: 99%
“…Both theoretical and experimental results in the literature have shown that SPR peak position depends on particle diameter, aspect ratio, shape, surface coating, surfactants, surface morphology, volume, coating of other nanoparticles, and aggregates of gold substrates. [45][46][47][48][49][50][51][52][53][54] Sigmoidal responses were observed as a function of the coverage of proteins (in log scale) on gold particles deposited on flat substrates. 55 This is similar to the Langmuir-Freundlich isotherm curve, 47 which is not an intrinsic response of silver layer on gold substrate.…”
Section: Resultsmentioning
confidence: 99%